Perancangan Aplikasi Penjadwalan Produksi Dengan Menerapkan Metode CPM (Studi Kasus: PT. Indojaya Agrinusa Medan) - Victor Surya Jaya Aritonang (KLIK: Kajian Ilmiah Informatika dan Komputer, 2021)
Scheduling (Scheduling) or making a schedule is one of the important activities in the production process or work of a project. Scheduling is used as the basis for allocating factory resources such as production machines and equipment, planning human resources to be used, purchasing materials and planning the production process. The scheduling process at PT Indojaya Agrinusa Medan currently still utilizes a bar graph with the design of each activity described in its entirety from the first activity to the last activity without explaining in detail the possibility that an activity can be postponed or declared as a critical activity, so that in the process of carrying out production often There is an increase in time or overtime which results in uncontrolled additional costs. The technique used is very supportive of the scheduling process because each activity will be defined when the activity starts the fastest and when the activity starts at the latest and also the completion of the activity and there is information for each activity so that when production is carried out the workers understand the next activity